The effect of the geometric parameters of the corrugation shape on the vibration analysis of 3D structured beams. (September 2017) - Robin, G.; Mathieu, N.; Jrad, M.; Daya, E.M.; Choquart, F.
Highlights: Vibration analysis of 3D structured beams by double sinusoidal pattern. Parameters: orientation, amplitude, wave length of the double sinusoid shape. Comparison of the experimental and numerical results. Resonant frequencies generally increase due to corrugated shape. Optimal value of the parameters can be found to increase the resonant frequencies. Abstract: This paper deals with the vibration analysis of 3D structured beams with double sinusoidal pattern. The corrugation depends on different parameters such as orientation, amplitude and wave length of the double sinusoid shape. First, a numerical modeling was built using the Finite Element method. Then, experimental tests of bending vibration were conducted on planar and corrugated beams. These data validated our model and proved that the resonant frequencies generally increase due to corrugated shape. A parametric study demonstrated that the optimal values of the corrugation shape can be found to increase the resonant frequencies.